DIKSI DAN CITRAAN NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Miftahul Rahmi; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this study (1) describes the new structure Tenggelamnya Kapal Van Der Wijck by Hamka, (2) to use the new diction of Tenggelamnya Kapal Van Der Wijck by Hamka. describe ; (3) to describe the use of the new image of Tenggelamnya Kapal Van Der Wijck by Hamka. This type of research is qualitative research with a descriptive method of analysis; it means analyzing and describing data descriptively. The data collection of this research with the aid of literature technique. The results of this research indicate that the structure of the novel Tenggelamnya Kapal Van Der Wijck by Hamka can be seen on the basis of the cohesion of friends and the facts of the story. The new theme of Tenggelamnya Kapal Van Der Wijck of Hamka is a love story that is hampered by the custom of a region. The main character in this novel is Zainuddin. The background used is Mengkasar, Minangkabau and Java. On the basis of the data analysis that was done, 162 data with the division (a) diksi 43 data with denotation data found 14 data, connotation 29 data. (b) footage 119 data with details of visual images 50 data, auditory image 20 data, moving image 42 data, image 4 image and 3 data tangible image.Keywords: Structure, images, novel tenggelamnya kapal van der wijck